Analisis Pengaruh Peran Guru dan Gaya Pengasuhan Orang Tua terhadap Pembentukan Karakter Siswa Dengan Model Persamaan Struktural - Junaedi, Lukman; Arif, Muchamad; virdaus, varia virdania; Widodo, Agung; Damastuti, Natalia; Latipah, Latipah (MOTORIC, 2025)
This study investigates the influence of teacher roles and parenting styles on character formation of students at Madrasah Ibtidaiyah Negeri 2 Sleman Yogyakarta. Overcoming the limitations of previous studies that used multiple linear regression, this study adopted Structural Equation Modeling (SEM) to model causal relationships between latent variables while controlling measurement errors. A sample of 200 students was selected through purposive sampling, with data collected via a Likert scale questionnaire 1-4 that has been validated through confirmatory factor analysis (? ? 0.70). Latent variables include: Teacher Role (X?) with 19 indicators (including motivators and facilitators), Parenting Style (X?) with 10 indicators (including democratic and responsive), and Character Formation (Y) with 24 indicators (including discipline and responsibility). The results of the SEM analysis showed a very good model fit (CFI=0.938; RMSEA=0.046; SRMR=0.048), revealing a significant influence of the Teacher's Role on Character Formation (?=0.36, *p*<0.001) and a stronger impact of Parenting Style (?=0.69, *p*<0.001). The findings also showed a high correlation between the two independent variables (?=0.71, *p*<0.001), confirming the synergy of the school-family environment. The dominance of the family's role in character education is balanced by the crucial contribution of teachers, with practical implications including democratic parenting programs, teacher training based on the role of motivators/facilitators, and holistic education policies. This study provides a methodological contribution through the application of SEM in the context of Islamic basic education as well as empirical validation of the ecological model of character formation.